The Influence of Education on Social Mobility and Economic Opportunities: A Review (International Journal of Social Science, Commerce & Management Studies, 2026)
Education has always been one of the most effective tools that can be used by individuals and societies to change the nature of their economic and social existence. This review paper brings together evidence from economics, sociology, and education policy from the past five years (2015-2024) to explore the complex connection between education, social mobility, and economic opportunity. The main thesis is that education serves two contradictory roles as a vehicle for upward mobility as well as a means of intergenerational transmission of inequalities. Education increases the individual income of the learner and provides more options when it comes to employment through human capital formation, the development of cognitive and non-cognitive skills, and the signaling of skills to the labor market. Aggregate level evidence shows that being widely educated is linked to increased intergenerational mobility, increased productivity and increased economic growth. But the distribution of the impact of education is very uneven. Education's equalising potential is limited by unequal access to quality education, stratification within higher education, the impact of family background and differential returns to credentials by social group. The review brings together evidence on the educational pay-off, intergenerational educational mobility, the role of higher education institutions, and the structural constraints to disadvantaged learning. It argues that the power of education to drive mobility is dependent upon the equitability of the access to and quality of education provided and that this must be part of the policy agenda. Future directions for research, such as longitudinal and cross-national designs, impact of digital transformation, and impact of emerging credentialing systems are described.
Keywords: education; social mobility; economic opportunity; human capital; intergenerational; inequality; returns to education